Employee Trust In General Manager And Performance Of Small And Medium Enterprises - MING, TEOH POH (2005)
The purpose of the research is to investigate the internal organizational characteristics underlying resource-based view, more specifically a trusted general manager, as a strategy leading to sustainable competitive advantage for small and medium enterprises. Also, the research attempts to determine the trust antecedents that provide general manager alternatives to influence the level of employees’ trust toward them.